Nicola Ignarra’s Encounter with a 3rd Century BC Neapolitan Coin Featuring SVESA in Reverse Field - Molinari, Nicholas J.; Clay, Curtis (KOINON: The International Journal of Classical Numismatic Studies, 2022)
Neapolitan overstrikes are quite common, no doubt because Neapolis appears to have served as the mint for much of the Campanian region for potentially up to two hundred years. In Nicola Ignarra’s 1770 work De Palaestra Neapolitana (‘Concerning The Wrestling School at Neapolis’) we find one of the earliest illustrations of an overstrike, where a Neapolitan bronze unit was overstruck on an undertype from Suessa. In researching the coin, however, it seems Ignarra had never seen an overstrike before, or not one like this, and so had really no idea what to make of the rather strange ‘inscription’ of SVESA appearing somewhat randomly on the reverse of an otherwise common Neapolitan coin. In this brief essay we’ll translate and analyze Ignarra’s account of the coin, discuss why it is indeed an overstrike, and identify the likely undertype and overtype.